1989
DOI: 10.1037/0882-7974.4.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of the classically conditioned eyeblink response in humans over the life span.

Abstract: Human subjects ranging in age from 18 to 85 years underwent classical conditioning of the eyeblink response to a tone conditioned stimulus (CS) and an air-puff unconditioned stimulus (UCS). There was a decline in percentage of conditioned responses with age. This decline was most noticeable in subjects over age 50. These conditioning deficits were not due to age-related changes in sensitivity to the tone CS or the air-puff UCS, nor could the conditioning deficits be attributed to an age-related decline in gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
124
5
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(143 citation statements)
references
References 35 publications
13
124
5
1
Order By: Relevance
“…Several studies have shown impaired conditioning with increasing age (Bellebaum & Daum, 2004;Knuttinen, Power, Preston, & Disterhoft, 2001;LaBar, Cook, Torpey, & Welsh-Bohmer, 2004;Solomon, Pomerleau, Bennett, James, & Morse, 1989;Woodruff-Pak & Thompson, 1988). In the present study, the age (61 years) of one member of the trace group fell in a range that has previously shown impairment relative to younger subjects (Bellebaum & Daum, 2004;LaBar et al, 2004).…”
Section: Discussionmentioning
confidence: 58%
“…Several studies have shown impaired conditioning with increasing age (Bellebaum & Daum, 2004;Knuttinen, Power, Preston, & Disterhoft, 2001;LaBar, Cook, Torpey, & Welsh-Bohmer, 2004;Solomon, Pomerleau, Bennett, James, & Morse, 1989;Woodruff-Pak & Thompson, 1988). In the present study, the age (61 years) of one member of the trace group fell in a range that has previously shown impairment relative to younger subjects (Bellebaum & Daum, 2004;LaBar et al, 2004).…”
Section: Discussionmentioning
confidence: 58%
“…Aging appears to progress at different rates in different individuals, producing a wide range of changes in neural systems, including those supporting learning and memory. Human subjects have demonstrable age-dependent heterogeneity in their ability to successfully acquire a conditioned eyeblink task (43). Increased variance in acquisition rates in rabbit eyeblink conditioning has also been reported, using a relatively simpler behavioral criterion (57).…”
Section: Discussionmentioning
confidence: 97%
“…Attention has been called to the fact that insufficient resources are currently available for studying brain aging (33,37), although the incidence of a variety of age-associated behavioral impairments in humans has climbed steadily as modern medicine has prolonged the average life-span in advanced countries (4,9,43,52). Two mammalian species have had widest use in behavioral and biological studies of aging, the rat (11)(12)(13)25,54) and the rabbit (41,46,52), although considerable work has been carried out with other species as well (18,20,36).…”
mentioning
confidence: 99%
“…terhoft, 2001; Solomon, Pomerleau, Bennett, James, & Morse, 1989;Solyom & Barik, 1965;Woodruff-Pak & Finkbiner, 1995;. These effects are dissociable from age-associated changes in the production of voluntary eyeblinks and baseline startle responses.…”
mentioning
confidence: 85%